Application of a commercial digestive supplement formulated with enzymes and probiotics in lactase non-persistence management. Issue 9 (29th August 2018) - Ferreira-Lazarte, Alvaro; Moreno, F. Javier; Villamiel, Mar
Abstract : Strategies to avoid lactose malabsorption, which affects 70% of the world's population, are focused on the restriction of milk and dairy products or the use of non-human β-galactosidases or probiotics endowed with β-galactosidase activity added at mealtime. Abstract : Strategies to avoid lactose malabsorption, which affects 70% of the world's population, are focused on the restriction of milk and dairy products or the use of non-human β-galactosidases or probiotics endowed with β-galactosidase activity added at mealtime. Our evaluation of a commercial blend of probiotics and enzymes (protease, lactase, lipase and amylase) and its potential application in lactase non-persistence management is described in this work. Recommended amounts (460–1000 mg) of the commercial probiotics–enzyme blend were shown to be adequate for performing in vitro lactose hydrolysis in standard solutions (0.25–5%) and commercial dairy products, namely milks (5% lactose) and yogurts (3% lactose), reaching hydrolysis values between 44 and 96%. According to these percentages, the use of the enzymatic preparation would guarantee the intake of less than 12 g, the recommendation of the EFSA for lactose intolerance. Furthermore, formation of prebiotic galactooligosaccharides was also detected, increasing the potential benefits of the enzymatic preparation in the gastrointestinal system.